Mechanisms of stress-induced martensitic transformation and transformation-induced plasticity in NiTi shape memory alloy related to superelastic stability. (August 2022) - Xu, Kengfeng; Luo, Jiao; Li, Cong; Shen, Yulu; Li, Chaojun; Ma, Xiao; Li, Miaoquan
Abstract: R and B2 nano-domains are introduced in NiTi shape memory alloy (SMA) through isothermal compression followed by post aging, and high superelastic stability is achieved. Results show that recovery ratios for as-deformed and as-aged NiTi in 10 loading-unloading cycles are 50.31%±6.28% and 92.19%±0.94%, respectively. A three-step shear stress-induced martensitic transformation (SIMT) in and between ( 0 1 ¯ 1 ) B 2 plane is proposed, resulting in transformation of B2→B19′+metastable B2 for as-deformed NiTi, and B2+ R →R→B19′+metastable B2 for as-aged NiTi. During unloading, inverse martensitic transformation-induced stacking faults (SFs) along { 211 } B 2 planes, dislocation multiplication and residual B19′ formation are reasons for plasticity and superelastic instability, indicating B19′+metastable B2→B2+SFs occurs in as-deformed NiTi. Furthermore, B19′+metastable B2→R→B2+ R occurs without SFs because of complex stacking sequence of R phase, rationalizing the superelastic stability of as-aged NiTi. This research opens an avenue to improve superelastic stability of NiTi SMAs by inhibiting the formation of transformation-induced SFs. Graphical abstract: Image, graphical abstract